Customizing elastic pressure bandages for reuse to a predetermined, sub-bandage pressure: A randomized controlled trial. (October 2018) - Sermsathanasawadi, Nuttawut; Tarapongpun, Tanakorn; Pianchareonsin, Rattana; Puangpunngam, Nattawut; Wongwanit, Chumpol; Chinsakchai, Khamin; Mutirangura, Pramook; Ruangsetakit, Chanean
Objective: A randomized clinical trial was performed to compare the effectiveness of unmarked bandages and customized bandages with visual markers in reproducing the desired sub-bandage pressure during self-bandaging by patients. Method: Ninety patients were randomly allocated to two groups ("customized bandages" and "unmarked bandages") and asked to perform self-bandaging three times. The achievement of a pressure between 35 and 45 mmHg in at least two of the three attempts was defined as adequate quality. Results: Adequate quality was achieved by 33.0% when applying the unmarked bandages, and 60.0% when applying the customized bandages ( p  = 0.02). Use of the customized bandage and previous experience of bandaging were independent predictors for the achievement of the predetermined sub-bandage pressure ( p  = 0.005 and p  = 0.021, respectively). Conclusion: Customized bandages may achieve predetermined sub-bandage pressures more closely than standard, unmarked, compression bandages. Clinical trials registration: ClinicalTrials.gov (NCT02729688). Effectiveness of a Pressure Indicator Guided and a Conventional Bandaging in Treatment of Venous Leg Ulcer.https://clinicaltrials.gov/ct2/show/NCT02729688